2014
DOI: 10.1155/2014/602034
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Importance of Fibroblast Growth Factor-23 in Dialysis Patients

Abstract: Introduction. In this study, we aimed to demonstrate the correlation of FGF-23 levels with bone-mineral metabolism, anemia, and the treatment in dialysis patients. Methods. Eighty-nine patients with similar age, gender, dialysis duration, and dialysis adequacy who were receiving hemodialysis replacement therapy for at least 6 months were included in the study. Serum iron, iron binding capacity, ferritin, hemoglobin (Hb), hematocrit (Htc), calcium (Ca), phosphorus (P), intact parathormone (iPTH), and FGF-23 le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…To date, there have been only five studies that have specifically addressed this issue. In a study by Akalin et al ., there was no association between FGF23 and hemoglobin levels in 89 patients undergoing hemodialysis 26 . In addition, a recent observational study by Honda et al .…”
Section: Discussionmentioning
confidence: 82%
“…To date, there have been only five studies that have specifically addressed this issue. In a study by Akalin et al ., there was no association between FGF23 and hemoglobin levels in 89 patients undergoing hemodialysis 26 . In addition, a recent observational study by Honda et al .…”
Section: Discussionmentioning
confidence: 82%
“… 12 , 13 Serum FGF23 level was found to increase once estimated glomerular filtration rate (eGFR) is lower than 90 mL/min/1.73 m 2 , 14 16 and was found to be associated with an increase of CVD, left ventricular hypertrophy, and mortality rate in both nondialysis and dialysis CKD patients. 17 , 18 Not only a direct effect of FGF23 on both pre and postnatal erythropoiesis inhibitions was recently reported in an animal study, 19 but also a positive correlation between FGF23 and hemoglobin (Hb) levels was portrayed in hemodialysis patients by Akalin et al 20 Meanwhile, a negative relationship had disclosed between serum FGF23 and aldosterone levels in another animal study, both of which may had an impact on renal anemia. 21 However, at present, this relationship between Hb and FGF23 levels is not available in nondialysis CKD patients.…”
Section: Introductionmentioning
confidence: 94%
“…However, studies evaluating this relationship have yielded conflicting results. In a study by Akalin et al, the authors showed a lack of association between FGF23 and hemoglobin levels in 89 hemodialysis patients [15]. Likewise, a study by Honda et al in a larger hemodialysis cohort showed no significant relationship between FGF23 and hemoglobin levels [16].…”
Section: Discussionmentioning
confidence: 95%
“…Thus, our results could explain some of the inconsistent findings in previous studies assessing the association between FGF23 and anemia. In the studies of Akalin and Honda [15,16], higher levels of P could have masked the true association between FGF23 and anemia. Indeed, those studies were performed in hemodialysis patients, a population in which P levels are usually higher than in other CKD stages [27].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation